Pengaruh Bimbingan Kelompok dengan Teknik Assertive Training dalam Meningkatkan Kepercayaan Diri pada Remaja - Rika Herdiana Rahman; Zhila Jannati; Lena Marianti (Journal of Society Counseling, 2025)
This study is entitled “The Effect of Group Guidance with Assertive Training Techniques in Increasing Self-Confidence in Youth Organization Teenagers in Pedamaran III Village”. This research is motivated by the fact that self-confidence plays an important role in all situations, because without it, education and social interaction in the educational environment and social environment will be greatly disrupted. Lack of self-confidence is caused by various factors, such as feelings of dissatisfaction with appearance, negative mindset, difficulty expressing feelings, and social pressure. Therefore, efforts need to be made to foster self-confidence, namely by using group guidance and assertive training techniques. The purpose of this study is to determine how the influence of group guidance with assertive training techniques increases self-confidence in youth karang taruna in Pedamaran III Village. This research method uses a quantitative approach with an experimental research type and one group pretest-posttest design. The research shows that the mean result of the pretest is 77, smaller than the mean value of the posttest, which is 134. So it can be seen that there is an increase in self-confidence in adolescents after treatment. This is shown from the paired sample t-test, resulting in a calculated T value of -15.138, a mean of 56.833, and a sig value. 0.001 <0.05. It can be concluded that Ho is rejected and Ha is accepted. So, group guidance with assertive training techniques has an effect in increasing the self-confidence of adolescents in the youth organization of Pedamaran III Village.